Upaya Bimbingan Konseling Berbasis Panggung Cerita Guna Meningkatkan Kecintaan Budaya Literasi Di Sekolah Dasar - Durrotun Nafisah; Ari Khusumadewi; Evi Winingsih; Mochamad Nursalim (Universitas Nusantara PGRI Kediri, 2024)
The literacy level of Indonesian students, as reported by PISA in 2018 and 2022, is considered low, falling below international standards. This situation contributes to learning difficulties and an increased risk of school dropouts. This study aims to analyze the role of story-stage-based guidance and counseling in enhancing the literacy culture in elementary schools. A qualitative approach was adopted, utilizing literature reviews and documentation techniques. The findings indicate that literacy is a fundamental element for students' personal development, both academically and socially, involving the acquisition and application of knowledge. Holistic guidance and counseling efforts are tailored to meet student's needs and are provided through counseling services. The story-stage method has proven to be an innovative and effective way to increase students' interest in literacy. It is recommended that this method be implemented in counseling services to strengthen the literacy culture in schools. Future research should focus on implementing and evaluating its effectiveness in broader educational contexts.